On Ways and Means of Expressing Satisfaction in the Russian Language - Andrey Yevgenyevich Bochkarev (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2017)
This article explores the ways and means of expressing satisfaction in the Russian language in order to show how the analysed emotional concept varies in everyday cognitive and volitional states of consciousness. According to the Russian National Corpus, satisfaction may be moral, mental, physical, sexual, narcissistic, sadistic or masochistic by nature; profound, deep, full or light by intensity; supreme or perfect by the moral evaluation; pleasant, pleasurable, bitter or painful regarding the physical sensations; happy, blissful, sad or humiliating regarding the emotional sensations; artistic, aesthetic, communist or Christian regarding the field of application; male, female, mutual or reciprocal regarding the subject participating. Satisfaction is also defined, in many different contexts, in relation to need, work, pleasure, delight, happiness, complacency, passion, curiosity, joy, etc. Such correlations may be explained by many human needs as well as many situations, causes or means of being satisfied. In this regard, the concept of satisfaction is diffuse like many other emotional concepts.